Short Communication: Early stability test of mutant candidates of Bangka local cassava, Indonesia - TRI LESTARI; ERIES DYAH MUSTIKARINI; RION APRIYADI; SAIPUL ANWAR (Society for Indonesian Biodiversity, 2019)
Lestari T, Mustikarini ED, Apriyadi R, Anwar S. 2019. Early stability test of mutant candidates of Bangka local cassava, Indonesia. Biodiversitas 20: 337-342. Cassava production in Indonesia has decreased due to decreased harvest area. Increasing production can be done by improving genetic diversity through gamma-ray irradiation to create high production mutant. The purpose of this study was to determine the optimum irradiation doses in relation to improve production of local cassava from Bangka Island, as well as morphological changes resulting from the irradiation. The research was conducted at the Experimental Garden, the University of Bangka Belitung, Indonesia in September 2017 until April 2018. This experiment was using Split Plot design, with the main plot consisted of 2 levels and subplot have 3 treatment levels, and 4 replications, in total there were 24 experimental units. The results showed that gamma-ray irradiation had very significant effect on plant height, number of leaves, young leaf color, stem color, and number of lobes. Gamma-ray irradiation on 3 Bulan accession showed an improved tuber production, whereas in Malang varieties gamma-ray irradiation decreased tuber production. Gamma-ray irradiation dose of 30 Gray was able to improve the number of tubers, tuber weight and starch content on 3 Bulan cassava accession.